A camp based screening of BMD in medical students: early detection of an iceberg phenomenon - Mishra, Santosh Kumar; Trivedi, Anshuli; Neelkanth, Namita; Trivedi, Anubhooti (International Journal of Research in Medical Sciences, 2018)
Background: Low Bone mineral density (BMD)/Osteopenia is an iceberg phenomenon. It is ignored by younger population and perceived as geriatric illness. As the study of medicine is very taxing its need of hour to detect low BMD amongst medical students to avoid musculo-skeletal disease due to low BMD in future. Methods: A DXA based technique was used to detect BMD amongst 72 under 25 years female medical students using nonrandom, opportunistic sampling technique. The data was collected in pre-designed pretested proforma and complied and analyzed using MS-Excel 2010 and Epi info-7.0. The data was expressed in percentages and proportions. Those with osteopenia were given appropriate medical advice. Results: In total 20.93% students had osteopenia and 55.56% participants had musculoskeletal complaints and most common being low back pain esp. in osteopenic participants. A statistically significant low level of BMD was observed amongst sunscreen users and physically inactive participants. No association was seen between BMD and BMI, regular, milk intake, type of diet or fasting. Conclusions: A significant number of female medical students were osteopenic and suffered from musculoskeletal disorders. A regular BMD assessment with calcium/vit D supplementation and regular physical exercise can restore/ conserve BMD. The currently available techniques can detect BMD in females but not in young males.